2021
DOI: 10.1021/acs.iecr.1c01610
|View full text |Cite
|
Sign up to set email alerts
|

CFD–PBE Model and Simulation of Continuous Antisolvent Crystallization in an Impinging Jet Crystallizer with a Multiorifice at Different Positions

Abstract: In this study, a comprehensive model which combines CFD and the population balance equation (PBE) was utilized to simulate the paracetamol continuous antisolvent crystallization. PBE was discretized using a high-resolution scheme and solved with the Eulerian multiphase model. The results indicated that the CFD–PBE model could successfully simulate the fluid dynamics, mass transfer, and crystal size distribution in the crystallizer. Based on the previously proposed multiorifice impinging jet crystallizer, an im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Additionally, an industrial large‐scale pharmaceutical production should consider the hydrodynamics of the crystallization process as another important factor. CFD simulations can be used as a powerful tool to optimize the reactor design, flow rate, agitation speed, and addition rate of species [106–111]. Both aspects mentioned require precise determination of the crystal's size, shape, polymorph, or other chemical/physical properties of the solution and species, which necessitate accurate in‐line measurement tools.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…Additionally, an industrial large‐scale pharmaceutical production should consider the hydrodynamics of the crystallization process as another important factor. CFD simulations can be used as a powerful tool to optimize the reactor design, flow rate, agitation speed, and addition rate of species [106–111]. Both aspects mentioned require precise determination of the crystal's size, shape, polymorph, or other chemical/physical properties of the solution and species, which necessitate accurate in‐line measurement tools.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…Wu et al found that the antisolvent crystallization was independent of mixing with the multiorifice-impinging transverse jet crystallizer due to its high mixing efficiency. Chen et al found that the mixing and crystal size in the multiorifice-impinging jet crystallizer can still be improved by a higher jet-to-cross-flow velocity ratio of 6 and a moderate feed point number of 3. Valeh-e-Sheyda and Mir found that the crystal size and CSD width decreased with the large confluence angle of 135° in the microchannel reactors.…”
Section: Phase Change For Separation and Purificationmentioning
confidence: 99%
“…Research on crystallizer modeling using computational fluid dynamics (CFD) simulation is ongoing. The population balance equation (PBE) proposed by Hulburt and Katz is widely used to predict the crystal size distribution (CSD). Coupled CFD–PBE research is being conducted actively for various crystallizer designs and operating conditions to improve the crystallizer performance. , However, such studies have mostly investigated nonslug tubular crystallizers. Tubular crystallizers, such as the Archimedes tube crystallizer and slug-flow crystallizer, , have also been subjected to many numerical studies.…”
Section: Introductionmentioning
confidence: 99%